Implementation of an intelligent caravan monitoring system using a simple serial communication protocol for microcontrollers (SSCPM) - Glocker, Tobias; Mantere, Timo (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Safety applications play an essential role in our daily life. Without them many accidents would have happened. Especially nowadays, where the amount of trafﬁc increases year by year, safety applications have become an important factor for the vehicle industry. Statistics have shown that the amount of accidents could be remarkably reduced for vehicles with safety systems. However, most of the safety systems are implemented on vehicles but not on trailers. This paper describes the implementation of an Intelligent Trailer Monitoring System which uses a Simple Serial Communication Protocol (SSCPM) for the communication between the vehicle’s board computer and the trailer’s monitoring system.
Keywords: fi=Tietoliikennetekniikka|en=Telecommunications Engineering|